Crimes against United Nations and Associated Personnel in Iraq - Amer Abbas, Sarmad; Nima al-Janabi, Ismail (International Journal of Psychosocial Rehabilitation, 2020)
In accordance with the purposes of the United Nations stipulated in Articles 1 and 2 of its Charter, and in the framework of implementing this, they need their own means and tools represented by the international personnel of the United Nations who carry out the task of conducting the work of the international organization. Terrorist crimes constitute a dangerous social phenomenon that threatens society and the lives, freedoms and security of individuals are in danger. It also affects relations between countries and violates the rules of general international law. The research sheds light on the appropriateness of national legislation in providing criminal protection regarding the safety of United Nations personnel and personnel associated with it, so that the protection is appropriate for them. With their major role in implementing the purposes of the United Nations through relief operations and humanitarian aid.